PERAN MEDIASI JOB RELATED TENSION PADA HUBUNGAN WORK FAMILY CONFLICT AND FAMILY WORK CONFLICT - Bernadetta Wiwik Wahyuningsih; Fransiskus Randa; Oktavianus Pasoloran (Magister Akuntansi, Universitas Atma Jaya Makassar, 2018)
This study aims to examine the effect of mediation job related tension on work family conflict and family work conflict. Job performance can increase due to job related tension, family work conflict dan work family conflict. Population of this study is the treasure of expenditure in the region of Makassar. The sample of this study is the treasurer of expenditure who working on the technical implementation/unit of work on Kantor Pelayanan Perbendaharaan Negara Makassar I. Data were collected using survey on 160 responden. This study indicates that job related tension variables in mediating the relationship between work family conflict against job performance is type No Mediation, it can be concluded that work family conflict does not have an indirect effect on job performance or in other words job related tension variables fail to function as intervening variables that mediate the influence of work family conflict on job performance. Then the job related tension variables that mediate the relationship between family work conflict with job performance is a type of full mediation. So it can be concluded that job related tension variables have an indirect effect on job performance.